Urine Density 1025 or 1.025 g/ml? - Traviezo Valles, Luis Eduardo (2020)
Reading with interest a clinical case published in the Journal of the Faculty of Human Medicine entitled, Primary Amyloidosis, the report of the density of the patient's urine was appreciated as 1000 (one thousand and without decimal places), when the correct one should have been 1,000 g / mL (one gram per milliliter), this is a very frequent error in sanitarians in Venezuela and other Latin American countries, so it is appropriate to remember the following elements: Density (ρ) is a scalar quantity that relates the amount of mass (g) that a certain volume (mL) presents. This principle was first described by Archimedes who, in order to authenticate the King's golden crown and not destroy it in the process, immersed it in a container with water and noted the volume of displaced (overflowing) water, then compared the displacement of the volume of water , but this time adding gold coins (compact shape), which should be the same weight of the crown (irregular shape) if the crown did not have other different alloys inside